2017
DOI: 10.5005/jp-journals-10015-1436
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Four most commonly used Pediatric Liquid Formulations in Ahmedabad City: An in vitro Study

Abstract: Introduction: This study was conducted to assess the cario genic potential of pediatric liquid medicaments (PLMs) of Allopathic, Homeopathic, Ayurvedic, and Unani formulations specifically in Ahmedabad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…35 Previous in vitro research showed that an acidic drugs can decrease enamel hardness and increase the enamel roughness. [38][39][40][41] Antimicrobials were the least water soluble seen among the different classes of drugs tested. A direct comparison could not be made as no previous studies were done on the solubility of ODTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Previous in vitro research showed that an acidic drugs can decrease enamel hardness and increase the enamel roughness. [38][39][40][41] Antimicrobials were the least water soluble seen among the different classes of drugs tested. A direct comparison could not be made as no previous studies were done on the solubility of ODTs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these factors, there can be a potential risk of dental erosion, decreased enamel hardness, increased roughness of tooth surface leading to plaque accumulation, demineralization of enamel, and rapid initiation and progression of dental decay. [38][39][40][41]50,51 Continuous usage of ODTs over a long time coupled with other risk factors like systemic comorbidities can cause the early onset and rapid progression of dentinal hypersensitivity, pain, rampant caries, and gum diseases. These can lead to poor aesthetics, functional limitations, and poor Oral Health-related Quality of Life.…”
Section: Discussionmentioning
confidence: 99%